2018
DOI: 10.1590/1809-6891v19e-47819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Chemotypes of Oregano Essential Oil on Broiler Performance, Nutrient Balance, and Lipid Peroxidation of Breast Meat During Storage

Abstract: This study evaluated the functional effects of two chemotypes of oregano essential oil (OEO): Lippia Origanoides (LO) and a comercial product Synergy Essence (SE). Broilers were randomly assigned to one of eight dietary treatments: 1) Basal diet (BD); 2) BD+ antibiotic growth promoters (AGP) (bacitracin 50g/ton); 3) BD+LO125 (125g/ton); 4) BD+LO250 (250g/ton); 5) BD+LO500 (500g/ton); 6) BD+SE125 (125g/ton); 7) BD+SE250 (250g/ton); 8) BD+SE500 (500g/ton). At the time of slaughter (42 d), five birds per treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
0
1
Order By: Relevance
“…Similar ADG results were also reported by Peng et al. (2016) at 300 and 600 mg/kg of feed of broilers and Ariza-Nieto et al. (2018) at 250 mg/kg of feed of broilers.…”
Section: Discussionsupporting
confidence: 89%
“…Similar ADG results were also reported by Peng et al. (2016) at 300 and 600 mg/kg of feed of broilers and Ariza-Nieto et al. (2018) at 250 mg/kg of feed of broilers.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with these studies, Peng et al (2016) observed that broilers treated with 600 mg OEO/kg had a lower percentage of abdominal fat than broilers treated with 300 mg oregano/kg diet and those in the negative and positive control groups. In contrast, Nieto et al (2018) did not observe any difference in abdominal fat in broilers treated with essential oils from two oregano species.…”
Section: Resultscontrasting
confidence: 65%